Prognostic clinical factors in patients affected by non-small-cell lung cancer receiving Nivolumab. (3rd March 2020) - Pantano, Francesco; Russano, Marco; Berruti, Alfredo; Mansueto, Giovanni; Migliorino, Maria R.; Adamo, Vincenzo; Aprile, Giuseppe; Gelibter, Alain; Ficorella, Corrado; Falcone, Alfredo; Russo, Antonio; Aieta, Michele; et al.
ABSTRACT: Background : Immune-checkpoint inhibitors have radically changed the treatment landscape of Non-Small-Cell Lung Cancer (NSCLC). It is still unclear whether specific clinical characteristics might identify those patients benefiting from immunotherapy more than others. The aim of this study was to identify clinical characteristics associated with disease-specific survival (DSS), time-to-treatment failure (TTF), objective responses (OR) and progressive disease (PD) in NSCLC patients treated with Nivolumab. Methods : This was a multicenter retrospective study conducted on 294 patients treated with Nivolumab for advanced NSCLC. Results : Of the more than 50 variables analyzed, five showed a significant correlation with DSS: ECOG PS, size of the biggest brain metastasis, number of metastatic sites, toxicity, and malignant pleural effusion. Three variables significantly correlated with TTF: malignant pleural effusion, number of metastatic sites, number of liver metastases. Malignant pleural effusion was the only variable showing a significant correlation with OR, as well as the only one correlating with all the endpoints of the study. Conclusions : This study identified clinical characteristics associated with survival and response during treatment with Nivolumab in NSCLC patients. The unfavorable association between malignant pleural effusion and objective response is a novel finding with important translational implications.